Ali uporaba ortoze za kolk z medenično košaro pri otrocih s cerebralno paralizo vpliva na zmožnosti sedenja in funkcijo rok? - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2017)
Introduction: Partial or complete dislocation of the hip is frequent in children with cerebral palsy (CP) who are not able to move independently (level IV and V of the Gross Motor Function Classification System, GMFCS). We found very little information about the potential effectiveness of Sitting, Walking and Standing Orthosis (SWASH). We wanted to check whether the use of SWASH affects sitting and hand function in children with CP. Methods: We included children with CP who were admitted to the University Rehabilitation Institute in Ljubljana, Slovenia, in the period from 1 march 2014 to 31 December 2014 and were fitted with a SWASH. We collected data on the child's age, GMFCS level, manual ability level (MACS), assessed spasticity in hip adductor muscles, measured the passive range of motion in hips and collected information on the Reimers migration index. To assess the possible effect of SWASH, we assessed function of hands and the ability to sit with and without SWASH at the beginning and at the end of the study, as well as six months later. Results: We included five children with CP (one at GMFCS level IV, four at level V). All of them already had increased Reimers migration index. All the children at GMFCS level V needed surgical treatment. Two children were able to sit better with the SWASH (exceeding minimal clinical important difference in GMFM-88 subscale for sitting). Three showed better hand function with SWASH (they needed from 20 % to 80 % less time to execute four test items: putting hand to table, pressing a switch, picking one block, and transfer five blocks). Conclusion: Given the small sample of included children, the conclusions are not reliable, but it seems that the children are able to sit still in a more stable way while using SWASH, and with more stable sitting they are able to show better hand function.
Keywords: Cerebral Palsy; cerebralna paraliza; Child; children; funkcija roke; hand function; Orthotic Devices; ortoza za kolk in koleno z medenično košaro; otrok; rehabilitacija; rehabilitation; sedenje; sitting; sitting, walking and standing hip orthosis; SWASH; vocational rehabilitation